2H/4H-Chromenes—A Versatile Biologically Attractive Scaffold - Raj, Vinit; Lee, Jintae (Frontiers in Chemistry, 2020)
2H/4H-chromene (2H/4H-ch) is an important class of heterocyclic compounds with versatile biological profiles, a simple structure, and mild adverse effects. Researchers discovered several routes for the synthesis of a variety of 2H/4H-ch analogs that exhibited unusual activities by multiple mechanisms. The direct assessment of activities with the parent 2H/4H-ch derivative enables an orderly analysis of the structure-activity relationship (SAR) among the series. Additionally, 2H/4H-ch have numerous exciting biological activities, such as anticancer, anticonvulsant, antimicrobial, anticholinesterase, antituberculosis, and antidiabetic activities. This review is consequently an endeavor to highlight the diverse synthetic strategies, synthetic mechanism, various biological profiles, and SARs regarding the bioactive heterocycle, 2H/4H-ch. The presented scaffold work compiled in this article will be helpful to the scientific community for designing and developing potent leads of 2H/4H-ch analogs for their promising biological activities.